Evaluation of Emergency Preparedness & Response (EPR) of commercial high-rise buildings in Kuala Lumpur / Badrul Hisham Ismail - Ismail, Badrul Hisham (Faculty of Architecture, Planning and Surveying, 2010)
A major emergency in a high rise building is one, which has the potential to cause serious injury, loss of life, fatality and serious damage both to human and environment. It may cause extensive damage to property and serious disruption both inside and outside building. Although the emergency may caused by a number of different factors, e.g. fire, explosion, earthquake or terrorist, it will normally give serious impact to the people and the property. Part of the emergency planning for any organization should include ensuring the ability of the organization to continue to function with a minimum disruption after a disaster. In the context of business continuity planning, a disaster is any event that could cause a period of total or partial interruption to normal business operations. This could be a fire or explosion or could be a much less dramatic event such as loss of power or telephone service. Management then needs to develop strategies for addressing each of the risks. The first goal is to prevent the risk from occurring. Since not all risks can be prevented with 100% certainty, the second goal is to minimize the impact on the organization if the event does occur. At all times the safety and protection of building users must be the primary consideration. Due to its potential destructive effect, it is organization responsibility to establish and maintain plans and procedures to identify the potential problems for and planned a response to incidents and emergency situations and for preventing and mitigating the likely illness and injury that may be associated with them. In 2001, the Fire and Rescue Department came up with guidelines (Jabatan Bomba dan Penyelamat Malaysia, 2001) on how to create an Emergency Response Programme (ERP) for the organisation. Besides that, all high-rise building is make compulsory to have a Fire Certification (FC) issued by BOMBA in order to ensure the high-rise is in good working condition and safe in term of building safety which has been enforce beginning from 23 July 1998 (Akta Perkhidmatan Bomba 1998) As describe in the act, any commercial which has exceeding than 30 meter height or 10,000 meter square of total floor area is made compulsory to have and annually renewed the Fire Certification (FC) issued by BOMBA without fail. The premise with FC must be connected either electrically or automatically using telephone with the nearest BOMBA station to cause the automatic alarm system at the connected BOMBA station trigger in the event of any emergency matters. (Akta Perkhidmatan Bomba 1998) A high-rise is a tall building or structure and normally the function of the building is added, for example high-rise apartment building or high-rise offices. High-rise buildings became possible with the invention of the elevator (lift) and cheaper, more abundant building materials. Thus, the effective emergency preparedness and response is required to minimise impact of major accident to the people, property and environment during emergency situation especially in congested and rapidly develop area like Kuala Lumpur. Extract from news paper. As of now there is 125 building in Klang Valley that does not have a fire certificate (FC) as required by the BOMBA according to Director General of Fire and Rescue Department, Datuk Hamzah Abu Bakar. Until Mac 2009, a numbers of 307 premises has obtain their FC and another 112 still in the midst of the getting their FC. (Sinar, 2009)